Molecular dynamic simulation on the stability of corporated metal organic framework and choline based ionic liquids - Ishak, M.A.I. (American Scientific Publishers, 2020)
A compatibility and stability of Isoreticuiar Metai Organic Framework (IRMOF-1) impregnated witli cigoline based ionic liquids (ILs) are studied by molecular dynamic simulation. Among three proposed IL7IRM0F-1 hybrid composites, cholinium formate, (ChlFm) is nominated as the best IL to be Incorporated with IRIVIOF-I since it shows the lowest RMSD value (0.502 nm, 0.637 nm, 0.923 nm) at three lUIRMOF-l w/w ratio (0.4%, 0.8% and 1.2%) respectively and become representative to all three ILs. Oxygen atom in the bridging carboxyl group shows the most flexible atom through RMSF analysis since it shows the highest fluctuation (1.001 nm) at WIL|IRMOF-1 = 0.4%. The RDF shows that the interaction between Chl+ and Fm- is higher in composite phase compare to bulky phase due to confinement effect of IRMOF-1. Both Chl+ and Fm- seem to be preferred to locate around carboxylate group inside the IRMOF-1 whereby Fm- shows the dominant interaction and strongly interacts with IRMOF-1 compared to Chl+. In terms of mobility, the cation shows high mobility with SDF value of 0.0419 nm2 in which mobility is expected to be increased with increasing of ILs ratio (0.4%, 0.8% and 1.2%) respectively. Intensity of the ions population around IRMOF-1 is interpreted by density map which is in agreement with the RDF analysis. Finally the stability of the IRMOF-1 is confirmed by the radius of gyration (Rg) analysis in which 0.4% ILs shows the most stable conformation with the lowest Rg value = 1.667 nm that is in consistent with the RMSD analysis. Overall, the structural stability of IRMOF-1 is well interpreted and impregnation of ILs literally increase the stability of framework at lower IL/IRMOF-1 w/w ratio. Copyright Â© 2020 American Scientific Publishers ALL rights reserved